2021
DOI: 10.1186/s12882-021-02293-2
|View full text |Cite
|
Sign up to set email alerts
|

Eculizumab therapy on a patient with co‐existent lupus nephritis and C3 mutation‐related atypical haemolytic uremic syndrome: a case report

Abstract: Background Thrombotic microangiopathy (TMA), a rare but serious complication of systemic lupus erythematosus (SLE), is associated with poor outcomes to conventional immunosuppressive therapy. Recently, eculizumab, a humanised monoclonal antibody that blocks the complement factor 5, has been known to effectively treat atypical haemolytic uremic syndrome (aHUS). Here, we report a case of aHUS co-existing with lupus nephritis that was successfully treated with eculizumab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that eculizumab, a new biological agent, has a potential therapeutic effect in LN with TMA. [15][16][17] However, these agents were not available at the time of the diagnosis and we could not assess their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that eculizumab, a new biological agent, has a potential therapeutic effect in LN with TMA. [15][16][17] However, these agents were not available at the time of the diagnosis and we could not assess their effectiveness.…”
Section: Discussionmentioning
confidence: 99%